Comparative study between the efficacy of Isobar TTL and Isobar EVO systems for lumbar degenerative diseases and their effects on adjacent segment degeneration - Zhang, Xiaozhe; Guan, Jianbin; Shi, Kesong; Wang, Tongzheng; Zhang, Yaqi; Li, Wei; Zhang, Tao; Yu, Xing; Zhao, Ziyi (Vojnosanitetski pregled, 2026)
Background/Aim. Lumbar degenerative diseases (LDD) are diseases that occur due to normal aging and degeneration of the lumbar spine. In addition to conservative therapies, surgical procedures become necessary to achieve satisfactory clinical outcomes. The aim of this study was to evaluate the effectiveness of the Isobar TTL and Isobar Evolution (EVO) systems of dynamic internal stabilization in the treatment of LDD and their effects on adjacent segment degeneration. Methods. This research involved 78 LDD patients treated with Isobar TTL or Isobar EVO dynamic internal stabilization devices. Patients were divided into two groups: TTL (n = 40) and EVO (n = 38). Visual Analog Scale (VAS) pain ratings, Oswestry Disability Index (ODI) scores, and modified MacNab criteria effectiveness evaluations were performed preoperatively, 1 and 3 months postoperatively, and at the final follow-up. Range of motion (ROM) and intervertebral space ratio (IVSR) were measured preoperatively and after the final follow-up. Results. In almost two years, 37 TTL and 33 EVO patients completed every examination. After surgery, VAS and ODI ratings in both groups improved significantly compared to preoperative levels (p < 0.05). The surgical effectiveness of the TTL and EVO groups was rated as excellent or good using the modified MacNab criteria (91.89% and 93.94%, respectively). Preoperative ROM and IVSR values did not differ between the groups (p > 0.05). At the final follow-up, the EVO group had a significantly higher ROM than the TTL group (4.46 ± 1.19° vs. 2.58 ± 0.71°; p < 0.05) and the ROM of adjacent segments in the TTL group was significantly higher than that of the EVO group (6.74 ± 1.55° vs. 5.83 ± 1.32°; p < 0.05). The IVSR of the operated and surrounding segments did not change substantially from preoperative to final follow-up (p > 0.05). Moreover, there was no significant difference in IVSRs between the two groups for the operated and neighboring segments at the final follow-up (p > 0.05). Conclusion. Isobar TTL and Isobar EVO dynamic stabilization systems demonstrated good clinical outcomes. The ability of Isobar EVO to inhibit neighboring segment motion may prevent degeneration.